Bacterial Communities Associated With Abnormal Nugent Score in Postmenopausal Versus Premenopausal Women. (27th October 2020) - Mitchell, Caroline M; Srinivasan, Sujatha; Ma, Nanxun; Reed, Susan D; Wu, Michael C; Hoffman, Noah G; Valint, Daniel J; Proll, Sean; Fiedler, Tina L; Agnew, Kathy J; Guthrie, Katherine A; Fredricks, David N
Abstract: The Nugent score is the reference standard for bacterial vaginosis (BV) diagnosis but has not been validated in postmenopausal women. We compared relative abundances from 16S ribosomal RNA gene sequencing of vaginal microbiota with Nugent score in cohorts of premenopausal (n = 220) and postmenopausal (n = 144) women. In premenopausal women, 33 taxa were significantly correlated with Nugent score, including the classic BV-associated taxa Gardnerella, Atopobium, Sneathia, Megasphaera, and Prevotella . In postmenopausal women, 11 taxa were significantly associated with Nugent score, including Prevotella but no other BV-associated genera. High Nugent scores should not be used to infer BV in postmenopausal women. Abstract : In postmenopausal women, an abnormal Nugent score (>3) was not associated with molecular detection of classic bacterial vaginosis (BV)-associated genera, such as Gardnerella, and may not represent BV.